The Influence of Company Reputation and Digital Marketing on Purchasing Decisions in the Tokopedia Marketplace by Cirebon City Consumers - Hammam Fadillah Azka; Fahad Rizky Wiguna; Lis Tatin Hernidatiatin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study is to analyze the role of company reputation and digital marketing on purchasing decisions of Tokopedia users in Cirebon. The testing method used in this study is Partial Least Square (PLS) based on Structural Equation Modeling (SEM) with primary and quantitative data. The study population is Tokopedia users in Cirebon, with a sample of 70 respondents selected through purposive sampling and online questionnaire distribution. The results of the study conclude that both variables of company reputation and digital marketing have a significant and positive influence on purchasing decisions by the people of Cirebon city on Tokopedia marketplace users. Most Tokopedia users in Cirebon city prefer to access information to assess the reputation of the company they are going to buy from social media and internet search engines as well as the Tokopedia website compared to e-mail when shopping on Tokopedia.